Penggunaan Media Word Wheel Untuk Meningkatkan Kemampuan Mengenal Huruf Siswa Sekolah Dasar Dalam Tahun 2015-2025 - Sanjung Ariesta Utami; Eko Handoyo; Ellianawati Ellianawati; Decky Avrilianda (Publikasi Indonesia, 2025)
Research on the use of word wheel media in improving letter recognition skills is a very important basic skill for primary school students as an early stage in learning to read and write. However, many students experience difficulties in recognising letters optimally, which can have an impact on their literacy development. This study aims to analyse the effectiveness of using Word Wheel media in improving letter recognition skills in primary school students. The research method used was an experimental method with a pre-test and post-test design. The research sample consisted of early grade elementary school students who were taught using Word Wheel media. The results showed that the use of Word Wheel media can significantly improve students' ability to recognise letters. This media provides a more interactive and fun learning experience that increases students' motivation in learning. Thus, Word Wheel can be an effective alternative learning media in supporting the development of students' early literacy skills.